1996
DOI: 10.1212/wnl.46.4.942
|View full text |Cite
|
Sign up to set email alerts
|

Silent cerebral infarction in patients enrolled in the TOAST study

Abstract: To determine the frequency, location, size, and risk factors for silent cerebral infarctions (SCIs) on brain CT, we identified 629 patients without a history of previous stroke who were enrolled in a multicenter clinical trial of therapy for acute ischemic stroke. On the baseline CT, 143 patients (22.7%) had SCIs; 34.3% of the lesions were in the right hemisphere, 38.5% in the left hemisphere, and 27.3% were bilateral. The lesion size was < 1 cm in 65.7%, and the most common site was the basal ganglia (48.3%).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 11 publications
4
30
0
Order By: Relevance
“…Similar to previous studies (Boon et al 1994;Davis et al 1996;Kobayashi et al 1997), the present study also demonstrated that the presence of hypertension was a significant independent determinant of the severity of cerebral white matter lesions. However, the results of the present study were different from those of the previous LVDs, left ventricular end-systolic dimension; LV D d , l e f t v e n t r i c u l a r e n d -d i a s t o l i c dimension; LVMI, left ventricular mass index; LVEF, left ventricular ejection fraction; E, peak early diastolic transmitral flow; A, peak late diastolic transmitral flow; E/A, the ratio of E to A; E′, peak early diastolic mitral annular velocity; A′, peak late diastolic mitral annular velocity; E′/A′, the ratio of E′ to A′; E/E′, the ratio of E to E′.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar to previous studies (Boon et al 1994;Davis et al 1996;Kobayashi et al 1997), the present study also demonstrated that the presence of hypertension was a significant independent determinant of the severity of cerebral white matter lesions. However, the results of the present study were different from those of the previous LVDs, left ventricular end-systolic dimension; LV D d , l e f t v e n t r i c u l a r e n d -d i a s t o l i c dimension; LVMI, left ventricular mass index; LVEF, left ventricular ejection fraction; E, peak early diastolic transmitral flow; A, peak late diastolic transmitral flow; E/A, the ratio of E to A; E′, peak early diastolic mitral annular velocity; A′, peak late diastolic mitral annular velocity; E′/A′, the ratio of E′ to A′; E/E′, the ratio of E to E′.…”
Section: Discussionsupporting
confidence: 91%
“…It is now established that cerebral white matter lesions are associated with a high risk of stroke (Miyao et al 1992;van Swieten et al 1992). Numerous studies have demonstrated that age and hypertension are highly and independently correlated with white matter lesions, i.e., with periventricular hyperintensity (PVH) and deep and subcortical white matter hyperintensity (DSWMH) (Boon et al 1994;Davis et al 1996;Kobayashi et al 1997). Kurata et al (2005) demonstrated that asymptomatic cerebral white matter lesions were related to carotid structure and hemodynamics, which have been demonstrated to be associated with the subsequent occurrence of stroke (Chambless et al 2000;Hollander et al 2002).…”
Section: Echocardiographic Examinationmentioning
confidence: 99%
“…The prevalence of silent lesions in previous CT or MRI studies varies from 10% to 47%, [6][7][8][9]23,24 and populationbased studies using MRI report a prevalence of silent lesions ranging from 11% to 28%. 2,25,26 In the present study, the prevalence of silent lesions by MRI, especially those ≥3 mm, was 44.9% in control patients, which is relatively high compared with previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] The reported prevalence of silent lesions observed by MRI varies, 3,[6][7][8][9] but there is consensus that it is high in elderly subjects and in patients with risk factors for stroke (eg, hypertension and atrial fibrillation (AF)). 1,4,10,11 The importance of these silent lesions has been emphasized in reports linking them to impaired cognition 2 and depression.…”
mentioning
confidence: 99%
“…The lesions are most frequently found in the basal ganglia 9 and periventricular white matter, which are not major areas that govern motor and sensory functions, but rather sites associated with coordination and the relay of signals through parts of the brain. However, the presence of cortical lesions and large lesions of Ͼ3 to 4 cm in diameter in subjects without noticeable neurological deficits still awaits elucidation.…”
Section: Lee Et Almentioning
confidence: 99%